WORD-FORMATION FEATURES OF PROTO-SLAVIC SOMATISMS - Ilona M. Prykhodko; Svitlana V. Podplota (Вісник університету ім. А. Нобеля. Серія Філологічні науки)
The naming of body parts, acting as one of the most noticeable layers of vocabulary, which reflects the knowledge of native speakers about the world around them, and their idea of both their own body and the body of animals, is the subject of constant attention of linguists. In modern linguistics, as in the humanities in general, the anthropocentric approach to the separation of somatic vocabulary prevails, when only parts of the human body are included in body parts. However, such a view of the realm of the corporeal and, moreover, the understanding of the pair “somatic – mental” only as one that applies to a man, denies the corporeality (however, as well as the realm of the psyche) of other living organisms ‒ animals. Therefore, we consider it appropriate to include the names of body parts of animals as somatic names. The article found that the Proto-Slavic language had a fairly extensive system of names of body parts. Many somatisms called parts of the body of both humans and animals. The somatic lexical subsystem includes such large groups of nouns to denote parts of the human and animal body, as: sonymic, osteonymic, splanchnonymic, angionimic, myonymic, sensonymic, neoplasmonimic. The object of study is the vocabulary to denote parts of the human and animal body, including the name of the head and its parts, neck and torso, skeleton and bones, cardiovascular and circulatory system, internal organs, muscles, human and animal senses, and also the names of neoplasms recorded in monuments of different styles and genres and historical dictionaries that reflect the vocabulary of the Proto-Slavic period. The purpose of the article is to carry out word-formation analysis of somatic names in the history of the Ukrainian language of the Proto-Slavic era. The main research methods are descriptive, comparative-historical, structural (component) analysis. The description of somatic names is carried out according to a complex method that combines semantic-word-forming and etymological aspects of the study. The authors found that the derivation of somatic names in the Proto-Slavic language occurred in two ways: by morphological and semantic word formation. The most productive, among morphological, way of word formation of somatic names of the pre-written period was suffixation, much less active in derivation of new words was confixation, prefix and composite word formation was represented by single formations. The peculiarity of the derivational semantics of somatisms on the territory of ancient Slavia is that some formants already lost their diminutive meaning in pre-written times. Non-morphological methods were represented by semantic derivation, when somatisms were created by transferring meaning on the basis of similarity, which later laid the foundations for the formation of a significant layer of somatic vocabulary. Prospects for the study are a more detailed analysis of the development and formation of somatic names in the dialects of the Ukrainian language, as well as the creation of principles for concluding a terminological basis of natural, including medical, sphere based on specific Ukrainian lexical material.